Cumulative Racial and Ethnic Disparities Along the School-to-Prison Pipeline. (August 2022) - Welch, Kelly; Lehmann, Peter S.; Chouhy, Cecilia; Chiricos, Ted
Objectives : Using the cumulative disadvantage theoretical framework, the current study explores whether school suspension and expulsion provide an indirect path through which race and ethnicity affect the likelihood of experiencing arrest, any incarceration, and long-term incarceration in adulthood. Methods : To address these issues, we use data from Waves I, II, and IV of the Add Health survey (N = 14, 484), and we employ generalized multilevel structural equation models and parametric regression methods using counterfactual definitions to estimate direct and indirect pathways. Results : We observe that Black (but not Latinx) individuals are consistently more likely than White persons to experience exclusionary school discipline and criminal justice involvement. However, we find a path through which race and Latinx ethnicity indirectly affect the odds of adulthood arrest and incarceration through school discipline. Conclusions : Disparate exposure to school suspension and expulsion experienced by minority youth contributes to racial and ethnic inequalities in justice system involvement. By examining indirect paths to multiple criminal justice consequences along a continuum of punitiveness, this study shows how discipline amplifies cumulative disadvantage during adulthood for Black and, to a lesser extent, Latinx individuals who are disproportionately funneled through the "school-to-prison pipeline."